ANALISIS DAYA DUKUNG LINGKUNGAN UNTUK JASA PENYEDIAAN PANGAN BERBASIS JASA EKOSISTEM DI KOTA PADANG - Ramadhani, Suci; Wilis, Ratna (JURNAL BUANA, 2024)
The city of Padang is the largest city on the west coast of Sumatra Island as well as the capital of the province of West Sumatra. So it has quite high economic and social activities. Due to population growth, the need for space will increase, while the amount of space that can be used is limited. This results in unavoidable land conversion which can threaten the sustainability and balance of the environment. In addition, in terms of food supply, it can be disrupted because the quality and quantity of the environment has decreased. Therefore it is necessary to conduct research related to the carrying capacity of the environment to support people's lives. In this study several analyzes were used, namely descriptive analysis, spatial analysis of land cover, and analysis of carrying capacity and environmental carrying capacity in Padang City. for food supply is classified as low, namely 59% of the total area of ​​the city of Padang